Pauline Donalda: The Life and Career of a Canadian Prima Donna - Brotman, Ruth C. (Eagle Publishing, 1975)
Pauline Donalda (1882-1970) was born Pauline Lightstone in Montreal. She adopted the name "Donalda" after her benefactor, Donald Smith, Lord Strathcona. She studied music at Montreal's Royal Victoria College and in Paris, and made her opera debut in 1904 in Nice, France. In 1922 she opened a studio in Paris and became a teacher, and in 1937 she returned to Montreal where she opened a studio. In 1942 she founded the Opera Guild of Montreal. She served as President and Artistic Director of the Guild until 1969.

La moitié du monde est une femme - Lemay, Jacqueline (Leméac Éditeur, 1975)

L'enseignement de la musique vocale et instrumentale aux Ursulines de Québec de 1830 à 1880 - Pagé, Thérèse (Université Laval, 1975)